USING SHORT STORY TO IMPROVE STUDENT’S READING COMPREHENSION (A Study at the Second Year Student of SMPN 2 Kota Bengkulu ) - Amelia Eka Frimasary (Linguists : Journal of Linguistics and Language Teaching, 2015)
The title of this research is Using Short Story to Improve Students' Reading ComprehensionAt the Second Year Students Of SMPN 2 Kota Bengkulu. The objective of this research wasto know the differences in students score and also to know whether the students interest wasimproved or not, after did a treatment using short story and handbook. The instrument of theseresearch was questionnaire. The result from short story was satisfactory. The mean score frompre-test was 45.1 for experimental class and 45.25 for control class. The differences both ofclass was 0.15 point. While the result of post-test was 55.9 for the experimental class and 51.8for the control class. The differences in both classes was 4.1. tt can be concluded that theexperiment was succesful. The explanation above shows that the differences in improvingstudents' score and interest by giving the treatment, and the differences score between twoclasses are significant. It means that reading activity by using short story could improvestudents reading comprehension in class I of SMPN 2 Kota Bengkulu.